Video-Based Project for Speaking Task - Nenda Widiyani; Berita M Nehe; Nunng Nurhayati (Program Studi Magister Tadris Bahasa Inggris UIN Sultan Maulana Hasanuddin Banten, 2022)
Abstract: This research was conducted to increase the speaking ability of eighth grade students of MTs. Darul Huda Cileles. Video-based project teaching is proposed in teaching speaking because it is interesting, especially for descriptive texts. Several previous studies found that video media can encourage kids to become more active and engaged willing to speak, so that their speaking skills can be improved. This study uses a classroom action research design. Researchers and teachers work together in designing lesson plans, criteria of success, action stages, observation stages, and reflections. The participants in this research were students in class VIII MTs Darul Huda Cileles for the academic year 2021/2022. This research was conducted by following action research procedures, namely planning, acting, observing, and reflecting. The percentage of students who achieved a score above the predetermined minimum completeness score (KKM) increased from only 20% (3 students out of 15 students) in the preliminary study to 50% (6 students out of 15 students). Students experienced a significant increase in scores obtained from video 1 and video 2. The first criterion was 11 students out of 15 students or 74% of students passed the KKM. For the second criterion, 74% of students are able to speak 8 sentences. For the third criterion, 74% of students are able to produce 8 sentences orally. After passing the research target where the criteria of success were 65% of students passed the KKM, and students passed the predetermined success criteria of 74%. For future researchers, it is recommended to conduct more than one preliminary study in order to identify the problem more accurately.